The 'terrorism' frame in 'neo-Orientalism': Western news and the Sunni–Shia Muslim sectarian relations after 9/11. (1st March 2014) - Douai, Aziz; Lauricella, Sharon
Sunni–Shia relations have become a topic of significant media attention; this attention is largely due to the tendency of these groups to engage in sectarian strife as well as the Islamic Shia sect's influential rise in world politics. The inter-Islamic sectarian relations are part of extensive reporting on upheaval events currently taking place in the Greater Middle East in the post 9/11 decade. This study analyses ten years of news coverage of the Sunni–Shia relations in the Canadian Globe and Mail and the US-based Washington Post. Results indicate that rather than contextualizing sectarian tensions between Sunni and Shia Islam, this media coverage overwhelmingly frames the tensions from the 'war on terrorism' perspective. This article argues that 'neo-Orientalist' discourses and propagandist perspectives have become routinized and more prevalent in the manner in which Western media represents Islam, privileging dominant discourses and 'war on terrorism' frames.